October overthrow in Serbia: The 5th of October 2000 - Atlagić Marko P.; Martinović Aleksandar I. (Baština, 2019)
With breakup of Yugoslavia and NATO aggression against FRY in 1999 aims of the USA and EU (Germany) strategic plan were achieved, especially in terms of their interests in Balkans and further breakthrough towards East. Final act of overthrow of legally elected authorities in Serbia and installation of marionette regime, which happened on the 5th of October 2000. Plan-makers were outside of FRY, but the executor was DOS (Democratic opposition of Serbia). Chanting "He is finished" reverberated like battle chant shortly before the elections in September 2000. Demonstrators were throbbing at pots, drums and bridge's fences, were blowing whistles, were writing graffiti, were blocking roads, but without effects. Thus, leaders of opposition sought help abroad. The political movement of "Otpor" (Resistance) played an important role in Milosevic's overthrow. 'Otpor' was organized, financed and led by USA, England and Germany. USA and Germany's plan overthrow actual leadership in Serbia in order to achieve dominant influence and the Balkans was the background of October events. During NATO aggression against Serbia and Montenegro, leader of Serbian opposition Zoran Đinđić fled from Serbia and found shelter abroad from where he advocating the continuation of NATO bombing until Milošević's overthrow, Srđa Popović, an attorney who signed one similar document, joined him as well. On the other hand, West did not ask how much it would cost to overthrow Milošević, and PH.D. Zoran Đinđić was receiving money. While the regular procedure for presidential election was going on in Serbia, West decided to stop it by helping the leaders of opposition. Demonstrators were taken out to the streets of Belgrade on the 5th of October 2000. Serbian Parliament was burned. Huge number of ballot paper was burned as well. Thus, it was impossible to determine the right result of elections. Rolling in dust, DOS came to power having no program for the country. USA and the EU promised help in getting rid of all those who tried to endanger DOS leadership, like PH.D. prof. Vojislav Šešelj. "Move Šešelj from Serbia" Zoran Đinđić requested on his knees before Karla Del Ponte, former ICTY prosecutor. According to Karla Del Ponte, Zoran Đinđić said he would extradite Milošević for the benefit of his country and his people. And, in case of emergency, even kidnap him, adding "give me another billion and he is yours". However, DOS was not capable to solve political problems and October the 5th remained only a lost battle for Serbia. "Otpor" destroyed Serbia by mugging privatization. Just an ideological symbol, clenched fist - clenched bunch of dollars - that is what remained from "Otpor".